Characterization of argon plasma in a variable multi-pole line cusp magnetic field configuration. (3rd February 2020) - Patel, A D; Sharma, M; Ramasubramanian, N; Ghosh, J; Chattopadhyay, P K
Abstract: This paper presents a detail characterization of argon plasma confined by a multi-pole line cusp magnetic field (MMF) over a large cylindrical volume (1 m axial length and 40 cm diameter) (Patel et al 2018 Rev. Sci. Instrum . 89 043510) and various magnetic field scaling with magnet current obtained from the magnetic field simulation in the vacuum. From the experimental results, it has been observed that in this field configuration the confinement of the primary electrons increases and leak width (plasma escaping through the cusp) of plasma decreases with increasing the magnetic field. As a result the mean density, particle confinement time and the stability of the plasma increase with increasing magnetic field values. In addition to this, it has been also observed that the radial uniformity of the plasma density across the magnetic field explicitly depends on the magnetic field values of MMF. Moreover, the nature of turbulence in a quiescent argon plasma has been identified.